Herbal cure for poisons and poisonous bites from Western Uttar Pradesh, India - Khan, Abdul Viqar; Ahmed, Qamar Uddin; Khan, Mohd Wasi; Khan, Athar Ali (Elsevier (Singapore) Pte Ltd, 2014)
Objective: To conduct ethnopharmacobotanical field explorations in rural areas of five districts of Uttar Pradesh, India with regard to the folk herbal formulations associated with the management of poisons and poisonous bites. Methods: Local traditional healers known as “Vaidya” and “Hakeems” in the study area were interviewed to gather ethnopharmacobotanical information using a questionnaire attending various medical practices. Results: Information on 49 herbal formulations prepared from 39 plant species belonging to 28 plant families in the treatment of poisons and poisonous bites is presented in this scientific communication. Conclusion: Present communication revealed that study area is rich in its ethnopharmacobotanical knowledge. The plant species discussed here also encompasses new reports on C. album, S. xanthocarpum, S. melongena, S. indicum, C. procera, C. sativum, C. dactylon, B. campestris, T. aestivum, V. vinifera, S. vulgare and N. indicum. This study further concludes that their lies a lot of potential in the Indian herbal repository which should be explored systematically and later subjected to thorough study under the light of latest available scientific investigations for the drug standardization and pharmaco-toxicological studies with respect to make cheaper and safer drugs for the benefit of ailing humanity encountered with poisons and poisonous bites.